Boosting Comprehension: Engaging Strategies for Teaching Reading - Dhakal, Basanta Raj (Journal of NELTA Koshi (JoNK), 2024)
Reading unlocks the doors to knowledge, imagination, and empathy. It is a gateway to knowledge to transform learners’ potential. Employing purposive sampling, this qualitative case study investigates engaging strategies to enhance reading comprehension based on semi-structured interviews and non-participant classroom observations of three basic level teachers. Five key themes emerged from the qualitative analysis of data: Activating prior knowledge, posing thought-provoking questions, summarizing key points, encouraging predictions, and fostering personal connections. These strategies were found to promote active reading, suggesting potential for wider implementation. Future research should examine their long-term impact on achievement and effectiveness in diverse settings.